Implementasi Algoritma Haversine pada Fitur Geolocation Aplikasi Pencarian Terapis Baby Spa - Mau'idzoh Hasanah; Carudin Carudin; Intan Purnamasari (Peneliti.net, 2023)
Based on 2014 national data from the Ministry of Health of the Republic of Indonesia, approximately 13-18% of infants and toddlers faced growth and development disorders, particularly in motor development. This heightened parental concern for their children's growth and development, leading to various efforts such as baby spa therapy. However, since the onset of the Covid-19 pandemic, there has been a shift towards seeking and ordering services online, including the search for therapists and booking of baby spa services. As a result, the need arises for a platform or application that enables users to find therapists and order baby spa services online. Although there is already a baby spa therapist application named Momby available on the Google Play Store, it still has limitations. The application lacks the ability to display the distance between the therapist and the user's location, causing inconvenience for users who are unable to travel long distances. This issue can be resolved by developing applications with geolocation features to locate baby spa therapists. The baby spa therapist search application is an Android-based system service designed to facilitate easy searching and ordering of baby spa services. This study aims to implement the Haversine algorithm within the Flutter framework and the Extreme Programming method to calculate the distance and provide users with the option to choose the therapist closest to their location. This study uses black box testing which concludes that the application functions properly and runs as expected.